List of Members, Associates and Junior Associates -Geographical (80532825-d294-479c-9af0-a25d3ab53a01) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
ALABAMA Anniston.-Bretz, J A Carnngton, F G Gerber, A B Ashland -Barton J Sturdevant, J C Bessemer -Abbott, C E Ball, T L Ferguson, V Salmon, H S Schaber, C F Thompson, N E Whatley, W J Birmingham.-Adams, J H -Aldrich, T H Aldrich, T H , Jr ALASKA Anchorage -Dyer, B W. Parker, H C Smith, S S Chichagof.-Baumann, H N , Jr Copper River.-Douglass, W C Cordova.-Hazelet, G C Fairbanks -Davis, J A Hyder -Pitt, D L Juneau -Jackson, G. T Murphy, R E R..11 ti At i